Volume 2: Emissions Control Systems; Instrumentation, Controls, and Hybrids; Numerical Simulation; Engine Design and Mechanical 2017
DOI: 10.1115/icef2017-3557
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Improve Combustion Stability, Efficiency, and Power Density of a Small, Port-Injected, Spark-Ignited, Two-Stroke Natural Gas Engine

Abstract: Two-stroke engines are often used for their low cost, simplicity, and power density. However, these engines suffer efficiency penalties due to fuel short-circuiting. Increasing power density has previously been an area of focus for performance two-stroke engines — such as in dirt bikes. Smaller-displacement engines have also been used to power remote controlled cars, boats, and aircraft. These engines typically rely on gasoline or higher-octane liquid fuels. However, natural gas is an inherently knock-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…To address these concerns, combustion systems have evolved over time, implementing a wide variety of approaches. Fuels are broadly utilized in premixed [1][2][3][4] and non-premixed combustion [5][6][7][8][9] using gas turbines and different forms of internal combustion (IC) engines such as spark ignition (SI) [10][11][12], homogeneous charge compression ignition (HCCI) [13][14][15], and reactivity controlled compression ignition (RCCI) [16,17]. Natural gas, as one of the cleanest fossil fuels, is one of the main sources of energy production and electricity generation in the United States and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns, combustion systems have evolved over time, implementing a wide variety of approaches. Fuels are broadly utilized in premixed [1][2][3][4] and non-premixed combustion [5][6][7][8][9] using gas turbines and different forms of internal combustion (IC) engines such as spark ignition (SI) [10][11][12], homogeneous charge compression ignition (HCCI) [13][14][15], and reactivity controlled compression ignition (RCCI) [16,17]. Natural gas, as one of the cleanest fossil fuels, is one of the main sources of energy production and electricity generation in the United States and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations using a port-injection (PI) configuration, I observed that two-stroke engines, even those with improved breathing and CR, suffered from fuel slip losses [57][58][59][60]. That is why direct injection was found to be necessary for energy optimization.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Alternatively, for two-stroke engines with fixed port geometries the exhaust design and exhaust throttling can serve as a method of inducing internal EGR. The lengths and angles of the convergent and divergent resonator sections directly impact the scavenging efficiency and thus level of internal EGR [10,18,42,44,46,59].…”
Section: Exhaust Gas Recirculationmentioning
confidence: 99%
See 2 more Smart Citations